Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Produk IT pada PT NQ Computer di Jakarta - Irvan Dwi Cahyo; Al Ghazali Al Ghazali (INDO PUBLISHING, 2026)
This study aims to analyze the influence of price and product quality on IT product purchase decisions at PT NQ Computer in Jakarta. The study was motivated by sales, profit, and customer numbers that have shown a tendency to fluctuate, making it necessary to identify the factors that influence purchase decisions. The theoretical framework draws on Indrasari’s concept of price, Kotler and Armstrong’s concept of product quality, Tjiptono’s theory of purchasing decisions, and a review of previous research. This study employs a quantitative approach using a saturation sampling technique involving 52 customers of PT NQ Computer. Data were collected through observation and a questionnaire using a Likert scale, then analyzed using validity and reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and the coefficient of determination with the aid of SPSS. The results indicate that price does not have a positive and significant effect on purchasing decisions (t = 1.082; p < 0.05), product quality has a positive and significant effect (t = 6.557; p < 0.05), and these variables simultaneously have a significant effect on purchasing decisions (F = 116.071; p < 0.05) with a coefficient of determination of 81.9%. This study recommends that PT NQ Computer evaluate its pricing strategy to remain competitive, improve product reliability through quality control and after-sales service, and strengthen its loyalty program and marketing communications to encourage customers to choose PT NQ Computer when purchasing IT products.